Pengaruh Kepemimpinan Transformasional, Kompensasi, dan Sarana Prasarana terhadap Kepuasan Kerja Guru yang Berimplikasi pada Kinerja Guru (Survei pada Guru di Sekolah Swasta Kecamatan Legonkulon Kabupaten Subang) - Nisa, Apriyani Iswatun; Somadi, Somadi (ALSYS, 2025)
Teacher performance is a key factor in improving educational quality, particularly in private schools, which often face challenges related to leadership, compensation, and the availability of facilities and infrastructure. Low job satisfaction among teachers can negatively impact motivation and work productivity, ultimately affecting the quality of instruction. This study aims to analyze the influence of transformational leadership, compensation, and facilities and infrastructure on job satisfaction and their implications for teacher performance in private schools in Legonkulon District, Subang Regency. A quantitative approach was employed, with data collected through questionnaires distributed to 133 teachers and analyzed using SmartPLS 4. The analysis involved both outer and inner model testing, presented through descriptive and verification techniques. The findings reveal that: (1) transformational leadership, (2) compensation, and (3) facilities and infrastructure each have a positive and significant effect on teacher performance; (4) job satisfaction also has a positive and significant effect on teacher performance; and (5) all four variables simultaneously exert a positive and significant influence on teacher performance, as indicated by the F-value exceeding the critical value (7.1 > 6.09). These results affirm that strengthening leadership, ensuring fair compensation systems, and providing adequate facilities and infrastructure enhance job satisfaction and directly improve teacher performance. The study’s implications serve as a reference for private school administrators in designing management policies that prioritize educator welfare and professionalism.